Transformational Leadership of the Madrasah Principal in Building a Religious Culture at Madrasah Ibtidaiyah - Muhammad Munir (Tarunateach: Journal of Elementary School, 2026)
The leadership of a madrasah principal plays an important role in determining the direction and character of Islamic educational institutions. In a Madrasah Ibtidaiyah, the principal not only serves as an administrator but also as a role model in cultivating religious values. This study aims to understand how the principal's transformational leadership is implemented in building a religious culture at Madrasah Ibtidaiyah Fathul Huda Pucung, Tulungagung Regency. The research uses a qualitative case-study design, with data collected from the principal, teachers, educational staff, and students. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed descriptively to identify patterns and meanings in the leadership practices observed in the field. The results of the study show that the principal, Mrs. SK, applies transformational leadership through role modeling, inspirational communication, and empowering teachers and students in religious activities. Religious values in the madrasah develop through routine activities such as congregational prayers, Qur’an recitation, and the consistent practice of courteous behavior. Leadership that emphasizes exemplary conduct and a spirit of togetherness has proven effective in fostering a vibrant religious culture that is embraced by all members of the madrasah community. The study concludes that transformational leadership is the key to shaping an educational environment that excels not only academically but also possesses strong religious character and spiritual meaning.